Referral patterns and proximity to palliative care inpatient services by level of socio-economic disadvantage. A national study using spatial analysis - Currow David C; Allingham Samuel; Bird Sonia; Yates Patsy; Lewis Joanne; Dawber James; Eagar Kathy (BMC, 2012)
Abstract Background A range of health outcomes at a population level are related to differences in levels of social disadvantage. Understanding the impact of any such differences in palliative care is important. The aim of this study was to assess, by level of socio-economic disadvantage, referral patterns to specialist palliative care and proximity to inpatient services. Methods All inpatient and community palliative care services nationally were geocoded (using postcode) to one nationally standardised measure of socio-economic deprivation - Socio-Economic Index for Areas (SEIFA; 2006 census data). Referral to palliative care services and characteristics of referrals were described through data collected routinely at clinical encounters. Inpatient location was measured from each person's home postcode, and stratified by socio-economic disadvantage. Results This study covered July - December 2009 with data from 10,064 patients. People from the highest SEIFA group (least disadvantaged) were significantly less likely to be referred to a specialist palliative care service, likely to be referred closer to death and to have more episodes of inpatient care for longer time. Physical proximity of a person's home to inpatient care showed a gradient with increasing distance by decreasing levels of socio-economic advantage. Conclusion These data suggest that a simple relationship of low socioeconomic status and poor access to a referral-based specialty such as palliative care does not exist. Different patterns of referral and hence different patterns of care emerge.